Nuclear Summer The Clash of Communities at the Seneca Women's Peace Encampment - Krasniewicz, Louise (Cornell University Press, 1992)
When thousands of women gathered in 1983 to protest the stockpiling of nuclear weapons at a rural upstate New York military depot, the area was shaken by their actions. What so disturbed residents that they organized counterdemonstrations, wrote hundreds of letters to local newspapers, verbally and physically harassed the protestors, and nearly rioted to stop one of the protest marches? Louise Krasniewicz reconstructs the drama surrounding the Women's Encampment for a Future of Peace and Justice in Seneca County, New York, analyzing it as a clash both between and within communities. She shows how debates about gender and authority-including questions of morality, patriotism, women's roles, and sexuality-came to overshadow arguments about the risks of living in a nuclear world. Vivid ethnography and vibrant social history, this work will engage readers interested in American culture, women's studies, peace studies, and cultural anthropology.